2016
DOI: 10.1016/s2352-3026(15)00283-5
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic plasma transfusion for surgical patients with abnormal preoperative coagulation tests: a single-institution propensity-adjusted cohort study

Abstract: Background Perioperative hemorrhage negatively impacts patient outcomes and results in substantial health care resource consumption. Plasma transfusions are frequently administered to address abnormal preoperative coagulation tests, with the hope of mitigating bleeding complications. This study aimed to evaluate the associations between preoperative plasma transfusion and bleeding complications in patients with elevated international normalized ratios undergoing noncardiac surgery. Methods An observational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…However, more recent studies have shown quite the reverse; that there is often a prothrombotic state, and transfusion of FFP has been described as usually unnecessary, ineffective and potentially hazardous. [139][140][141][142][143][144][145] A recent Cochrane review concluded that there is uncertainty about the utility and safety of prophylactic FFP use. 146 Thus, use of FFP is rarely indicated.…”
Section: Coagulation Testingmentioning
confidence: 99%
“…However, more recent studies have shown quite the reverse; that there is often a prothrombotic state, and transfusion of FFP has been described as usually unnecessary, ineffective and potentially hazardous. [139][140][141][142][143][144][145] A recent Cochrane review concluded that there is uncertainty about the utility and safety of prophylactic FFP use. 146 Thus, use of FFP is rarely indicated.…”
Section: Coagulation Testingmentioning
confidence: 99%
“…38 Similarly, multiple investigations have observed higher rates of bleeding complications in patients that receive prophylactic plasma transfusion for the management of elevated INR values in the absence of clinical bleeding. 3941 …”
Section: Discussionmentioning
confidence: 99%
“…38 Similarly, multiple investigations have observed higher rates of bleeding complications in patients that receive prophylactic plasma transfusion for the management of elevated INR values in the absence of clinical bleeding. [39][40][41] As another study limitation, plasma transfusion volumes were modest (median, 8.9 mL/kg), and hence "suboptimal" plasma dosing may have affected study results. Furthermore, most transfusions were administered with INR values less than 2 and hence within the range of potentially "preserved" hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…95 Whereas the evidence for the benefits of blood products in perioperative medicine is low, the supporting evidence for transfusion-related complications including transfusion associated lung injury, transfusion-associated circulatory overload, and infectious complications are increasingly acknowledged. 62 As in other types of surgery, 96,97 transfusion of blood products during liver surgery and liver transplantation has been associated with increased morbidity and mortality. 4 Our current practice is in general one of wait-and-see approach to start blood product transfusion only in actively bleeding patients with evidence of hemostatic abnormalities.…”
Section: Prevention and Treatment Of Bleedingmentioning
confidence: 99%